Leaders Vertical Coordination To Community in The Development Implementation - nurpeni; fara meriyan sari (Jurnal Niara, 2020)
Research with the title Vertical Village Coordinating Leaders to the communityin the implementation of development in the Wonorejo Village Marpoyan Damai District Pekanbaru City was held for about five months, where a phenomenon that often occurs where the problem of floods and accumulated rubbish always becomes an annual problem in the Kelurahan. Besides that, the implementation of community empowerment in the form of skill improvement is still less attractive to the community. This condition is inseparable from the lack of communication by village leaders to the community. The concept of theory in this study refers to the concept of James D. Money in the Shafi Inu Kencana (2011: 35) the elements that exist in coordination include:1. Settings, 2. Synchronization, 3. Common Interests, 4. Common Goals with data collection techniques through observation and in-depth interviews. The type of research is done through a qualitative descriptive approach. The results of the study showed that there was a lack of public knowledge about regulation, synchronization, shared interests and shared goals, this was due to the lack of communication by village leaders to the community and also the lack of socialization about the importance of environmental cleanliness.